Application of Taro Beneng Inulin and Red Dragon Fruit Peel Extract in Making Ice Cream - Vega Yoesepa Pamela; Fitria Riany Eris; Septariawulan Kusumasari; Dina Riziani (Universitas Teuku Umar, 2023)
The characteristics of ice cream with the addition of beneng taro inulin and red dragon fruit extract were evaluated in this study. Various concentrations of beneng taro inulin (3%, 4%, and 5%) and dragon fruit extract (25%, 30%, and 35%) were added as fat substitutes and natural dyes, respectively. The results showed that the addition of 4% taro beneng inulin had a significant effect on the overrun value, melting time, and fat content of ice cream. The addition of 30% red dragon fruit peel extract significantly affected the color of ice cream, fat content, antioxidant activity, and total plate number. There is an interaction between the treatment of the addition of taro beneng inulin and red dragon fruit peel extract on color analysis, namely the L* notation (brightness) and a* notation (redness). A3B3 ice cream was selected as the best ice cream formula based on existing criteria